PTH-006 Current Performance Of Ercp In The Clearance Of Bile Duct Stones In Uk Centres - Working Towards Robust Key Performance Indicators. (9th June 2014) - Wadsworth, CA; Dwyer, LK; Paranandi, B; Philips, N; Mahmood, S; Krishnan, B; Taylor, TL; Seward, E; Wilson, P; Singhal, A; Williams, E; Westaby, D; et al.
Abstract : Introduction: Choledocholithiasis is the commonest indication for endoscopic retrograde cholangiopancreatography (ERCP). ERCP carries substantial risk of complication when compared to other endoscopic modalities. The identification of key performance indicators (KPIs) in colonoscopy practice and implementation of related standards has driven quality assurance in the UK and elsewhere. The failure to establish similar contemporary, meaningful and measurable KPIs in ERCP has hampered the development of national standards. We aimed to quantify current performance in a potential new endoscopic KPI: the complete clearance of CBD stones at first ERCP. Methods: Seven centres participated – four secondary and three tertiary HPB units. All patients undergoing first ERCP for confirmed or suspected choledocholithiasis over a twelve month period were included and data were analysed on an intention to treat basis. The primary endpoint was complete clearance of bile duct stones. Failure to clear stones was defined as i) persisting stones reported ii) placement of biliary endoprosthesis, even if considered precautionary. Secondary endpoints were CBD cannulation, successful biliary decompression and complications. Outcomes were analysed by unit and by consultant clinician performing the procedure. Results: 1178 patients were included in the study. 20 consultant endoscopists carried out or supervised the procedures. Overall, deep biliary cannulation was achieved in 1074/1178 (91%, range for seven units 82–96%). Complete bile duct clearance at first ERCP was achieved in 861/1178 (73%, 65–81%). Conclusion: We investigated the outcome of 1178 ERCP procedures, representing real-life practice in the UK. Duct clearance was possible at first ERCP in almost three quarters of patients. There were significant differences in performance between units and individual operators. The reasons for this are not fully elucidated. The primary endpoint of this study has strengths as a potential KPI. It is clearly defined, measurable on an intention to treat basis and is strongly focused on patient outcome. In addition, it quantifies performance in the commonest indication for ERCP, stone extraction, which is undertaken in all ERCP units. Disclosure of Interest: None Declared.